Darriwilian (Middle Ordovician) chemostratigraphy linked to graptolite, conodont and trilobite biostratigraphy in the Fågelsång-3 drill core, Scania, Sweden*. (3rd July 2018) - Bergström, Stig M.; Ahlberg, Per; Maletz, Jörg; Lundberg, Frans; Joachimski, Michael M.
Abstract: A recent core drilling in the geologically classical Fågelsång area resulted in a 58.70-m-long drill core through the lowermost Sandbian Sularp Shale, the Darriwilian Almelund Shale and Komstad Limestone, and part of the late Tremadocian to earliest Darriwilian Tøyen Shale. The shales contain zone index graptolites that are used for an update of the standard Darriwilian graptolite zone succession in Baltoscandia in which six zones are now recognized. The Komstad Limestone interval and lowermost part of the Almelund Shale have been subdivided into four conodont zones. The δ 13 Corg chemostratigraphy, which has been established through the entire drill core based on 120 closely spaced samples, shows a somewhat subdued development of the middle Darriwilian Isotope Carbon Excursion (MDICE), which is dated in terms of graptolite biostratigraphy. The Fågelsång isotope curve is correlated with a closely similar δ 13 Ccarb curve from a coeval, apparently stratigraphically essentially continuous, succession at Kårgärde in south-central Sweden, which previously has been subdivided into 13 conodont zones and subzones. For the first time, these conodont zonal units can be calibrated with Fågelsång graptolite zones using δ 13 Corg chemostratigraphy. The several new results of this study are expected to be useful for assessing biostratigraphic relations between units in shale and carbonate facies in Baltoscandia and elsewhere in the world.